Theory of Potential with Respect to Consistent Kernels; Theorem on Completeness and Sequences of Potentials - Zorii, N. V. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
The concept of consistent kernels introduced by Fuglede in 1960 is widely used in extremal problems of the theory of potential on classes of positive measures. In the present paper, we show that this concept is also efficient for the investigation of extremal problems on fairly broad classes of signed measures. In particular, for an arbitrary consistent kernel in a locally compact space, we prove a theorem on the strong completeness of fairly general subspaces E of all measures with finite energy. (Note that, according to the well-known Cartan counterexample, the entire space E is strongly incomplete even in the classical case of the Newton kernel in ℝn Using this theorem, we obtain new results for the Gauss variational problem, namely, in the non-compact case, we give a description of vague and (or) strong limiting measures of minimizing sequences and obtain sufficient solvability conditions.